HUBUNGAN ANTARA GAMBARAN SITOLOGIS DENGAN METODE FNAB DAN RESPONS TERAPI PADA PASIEN LIMFADENITIS TUBERKULOSIS DI RSUD PROVINSI NTB PADA TAHUN 2019 - Halidagia Reksadita Lugina gia (Unram Medical Journal, 2021)
Introduction: Indonesia is a country with the highest Mycobacterium tuberculosis infection along with 48 other countries. About 60 – 90% cases of Mycobacterium tuberculosis infection infects the lymph nodes in the cervical region. The use of the fine needle aspiration biopsy (FNAB) method in the examination of enlarged lymph nodes is an accurate minimally invasive technique and is widely applied. Method: This is an observational analytic study with total sampling method. The data were obtained by documenting the medical records of tuberculosis lymphadenitis patients who were treated at the RSUD Provinsi NTB in January to December 2019. The research subjects were 50 patients. The analysis was performed by Spearman correlative hypothesis using SPSS 25.0. Result: The total number of study subjects was 50 people (5 patients with type-1 cytological features, 20 patients with type-2 cytological features, and 25 patients with type-3 cytological features). Correlation of cytological features with enlarged lymph nodes and weight loss was < 0.005, whereas the therapeutic response in the form of fever showed a value of > 0.005. Conclusion: There was a significant relationship between cytological features and lymph node enlargement and weight loss after taking anti-tuberculosis drugs for at least 6 months, while the association between cytological features and the incidence of fever was not significant.